Long‐term safety and efficacy of eculizumab in generalized myasthenia gravis. Issue 1 (8th March 2019) - Muppidi, Srikanth; Utsugisawa, Kimiaki; Benatar, Michael; Murai, Hiroyuki; Barohn, Richard J.; Illa, Isabel; Jacob, Saiju; Vissing, John; Burns, Ted M.; Kissel, John T.; Nowak, Richard J.; Andersen, Henning; et al.
ABSTRACT: Introduction : Eculizumab is effective and well tolerated in patients with antiacetylcholine receptor antibody‐positive refractory generalized myasthenia gravis (gMG; REGAIN; NCT01997229). We report an interim analysis of an open‐label extension of REGAIN, evaluating eculizumab's long‐term safety and efficacy. Methods : Eculizumab (1, 200 mg every 2 weeks for 22.7 months [median]) was administered to 117 patients. Results : The safety profile of eculizumab was consistent with REGAIN; no cases of meningococcal infection were reported during the interim analysis period. Myasthenia gravis exacerbation rate was reduced by 75% from the year before REGAIN ( P  < 0.0001). Improvements with eculizumab in activities of daily living, muscle strength, functional ability, and quality of life in REGAIN were maintained through 3 years; 56% of patients achieved minimal manifestations or pharmacological remission. Patients who had received placebo during REGAIN experienced rapid and sustained improvements during open‐label eculizumab ( P  < 0.0001). Discussion : These findings provide evidence for the long‐term safety and sustained efficacy of eculizumab for refractory gMG. Muscle Nerve 2019 Abstract : See editorial on pages 7–9 in this issue .